KAJIAN TENTANG PENYEBAB TRANSMIGRAN BERTAHAN TINGGAL DI DESA TIRTA KENCANA - Nurul Hasanah; Buchori Asyik; I Gede Sugiyanta (JPG (Jurnal Penelitian Geografi), 2013)
Tirta Kencana is one of the villages which became the settlement of transmigrant from Java in the year 1973/1974. Location hebitable be supporting settlement that transmigrants remain in transmigration sites. In addition, the area of land they have also influenced decisions to survive. Traditional still life in Java have implications for the economic life of the family and next-generation transmigrants. The issue of land and the narrowing of the rampant crime situation in the village was not making transmigrants in Tirta Kencana move to another place. This situation is interesting to study so that the purpose of this study was to determine the cause of transmigrants survive living in Tirta Kencana subdistrict of Tulang Bawang Tengah regency of Tulang Bawang Barat in 2012. The population in this study as many as 329 migrants. Samples taken are as many as 66 samples with Proportional Random Sampling technique in seven hamlets. The method used is descriptive method and data collection techniques are observation, structured interviews and documentation. Data analysis techniques using frequency tables and cross-tabulations as the basis for describing the data obtained and responding to expressed. The results showed that transmigrants endure living in the village of Tirta Kencana subdistrict of Tulang Bawang Tengah regency of Tulang Bawang Barat in 2012 because 1) The availability of facilities and adequate transportation infrastructure (89.4%), 2) as well as the relatives who have blood relations (98.5%). As for 3) Land owned (60.6%) is caused migrants to survive living in the village of Tirta Kencana and 4) ownership of valuable goods is not proven to be the cause of migrants survive living in the village of Tirta Kencana (48.5%).Key words: Last recidence, location of transmigration